2016
DOI: 10.1039/c6cp02999j
|View full text |Cite
|
Sign up to set email alerts
|

CO chemisorption at vacancies of supported graphene films: a candidate for a sensor?

Abstract: We investigate CO adsorption at single vacancies of graphene supported on Ni(111) and polycrystalline Cu. The borders of the vacancies are chemically inert but, on the reactive Ni(111) substrate, CO intercalation occurs. Adsorbed CO dissociates at 380 K, leading to carbide formation and mending of the vacancies, thus preventing their effectiveness in sensor applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…1, we can derive the probability of creating a vacancy by an incident ion, because it shall equal the slope of the curve for low doses, and we can derive from our data that this value is about 0.02. Note that the required doses are very similar to that published24.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…1, we can derive the probability of creating a vacancy by an incident ion, because it shall equal the slope of the curve for low doses, and we can derive from our data that this value is about 0.02. Note that the required doses are very similar to that published24.…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, a recent work explores the catalytic activities promoted by the unsaturated dangling bonds that may remain on a surface after SAV formation24. However, those experiments were performed on epitaxial graphene on metals, and it has been shown by DFT calculations that the C atoms at the vacancy edge back-fold towards the metallic substrate promoting bonding with it (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single layer G films were grown in situ by surface catalysed dehydrogenation of ethene, according to well established recipes. 11,15 The substrate growth temperature (T g ) was varied between T g = 753 K and T g = 873 K, for the different growth protocols. Ethene was introduced into the UHV chamber through a doser placed ∼1 cm away from the Ni(111) surface.…”
Section: Methodsmentioning
confidence: 99%
“…8 In a recent investigation, we have demonstrated that weak CO chemisorption occurs at pristine G/Ni(111) sites 9,10 while a G layer grown on polycrystalline Cu is unreactive under identical conditions. 11 The value of the desorption energy of CO/G/Ni(111) as well as its reversible nature indicates the occurrence of non-dissociative chemisorption at pristine sites up to a coverage as high as 0.33 monolayers (MLs). This unexpected result indicates that the nature of the substrate and the strength of its interaction with G are critical in determining the a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%